Three Kentucky artists--Hart, Price, Troye - Coleman, J. Winston, Jr. (John Winston), 1898-1983 (Kentucky Bicentennial bookshelf., 2009)
The three artists whose lives are the subjects of Three Kentucky Artists -- Joel Tanner Hart, Samuel Woodson Price, and Edward Troye -- enjoyed considerable fame in their own day, though they are now little known outside of Kentucky. Each made a lasting contribution to the social and cultural life of central Kentucky in the nineteenth century. J. Winston Coleman, Jr. sketches the careers and relationships of the artists who played significant roles in the hist.